Akamboja gen. nov., a new genus of railroad-worm beetle endemic to the Atlantic Rainforest, with five new species (Coleoptera: Phengodidae, Mastinocerinae) - Roza, André Silva; Quintino, Hingrid Yara Souza; Mermudes, José Ricardo Miras; Silveira, Luiz Felipe Lima Da (Zootaxa, 2017)
The Atlantic Rainforest is a hotspot of biodiversity, housing several endemic species. Environmental stasis through broad time scales, vast latitudinal extension and landscape heterogeneity are thought to contribute in explaining the greater species richness of this biome. Unfortunately, it is threatened mainly due to anthropic-driven habitat loss. Ectotherms of low-mobility, such as tropical, small soft-bodied railroad-worms, may be especially threatened by anthropogenic climate changes. Many of such species have narrow climatic niches and therefore might become extinct before we know them. Here we describe a new genus endemic of the Atlantic Rainforest mountain ranges, and five spatially disjunct new species. Akamboja gen. nov. is unique by its ten-segmented antenna, IV to VIII with two short symmetrical branches, branches of antennomere IX fused in a singular flabellum, slightly depressed medially; elytron short, surpassing the second to fourth abdominal segment (depending on species); first tarsomere of anterior leg with a ventral comb; claws with six long and asymmetrical teeth; aedeagus with patch of bristles at paramere apex. We provide a key to species as well as illustrations for the diagnostic features. We highlight that Akamboja cleidae sp. nov., as defined here, has a disjunct distribution and its populations are surrounded by an unsuitable environmental matrix, thus are probably reproductively isolated. Future phylogenetic studies should address the evolutionary history and delimitation of this taxon. We also provide a key to genera of Mastinocerinae with ten antennomeres, including Akamboja gen. nov.